(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Effective teaching and learning are underpinned by systematic planning that aligns instructional goals with curriculum standards. This paper critically examines the process of educational planning within the context of schools, lyceums, and colleges, with particular emphasis on the interpretation and practical application of syllabi. The syllabus functions as a macro-level framework that defines learning outcomes, content scope, assessment strategies, and time allocations, all of which inform the micro-level structure of individual lesson plans.